LEXICAL PITFALLS IN POLISH-ENGLISH LEGAL TRANSLATION: A CASE STUDY INVOLVING STUDENTS OF ENGLISH PHILOLOGY IN POLAND - ZYGMUNT, Łukasz (Comparative Legilinguistics, 2012)
The article illustrates problems which were encountered by students of the first and second year of English Philology, who had been given a task of translating from Polish into English a passage from a Supreme Court act, concerning the European Arrest Warrant execution. The author who is an active lawyer – working as a prosecutor of the District Prosecutor’s Office – analyzes almost twenty legal phrases coming from the original text and, comparing them with the official version of translation, examines the students’ versions (108 translations altogether) which are then accompanied by descriptions and comments on the mistakes made. The analyzed examples show the uniqueness of the legal language and its pitfalls as well as lexical and syntactic dilemmas which create linguistic traps for a Polish translator who is preoccupied with translation of legal texts from Polish into English or vice versa. Moreover, the discussed cases indicate the need for a highly professional training of philology students, especially in the area of ESP (English for Special Purposes).